Evolving management of low grade glioma: No consensus amongst treating clinicians. (January 2016) - Field, K.M.; Rosenthal, M.A.; Khasraw, M.; Sawkins, K.; Nowak, A.K.
Abstract: Following the widely publicized presentation of the Radiation Therapy Oncology Group (RTOG) 9802 data, we sought to understand how these data had been translated to the management of low grade gliomas (LGG) by Australian neuro-oncology clinicians. The de novo management of LGG is transitioning to include postoperative radiotherapy and chemotherapy after the RTOG 9802 study results demonstrated a survival benefit in this setting. In 2014, neurosurgeons, radiation oncologists and neuro-oncologists who were members of the Australian Cooperative Trials Group for Neuro-oncology (COGNO), as well as additional attendants of the COGNO annual scientific meeting, were surveyed. The survey presented six LGG clinical scenarios and asked respondents to select their preferred management strategy. Some additional questions included the respondents' approach to 1p/19q testing and chemotherapy preferences. The response rate was 30.2% (61/202), with the majority (77%) working in tertiary referral neuro-oncology centers. There was no consensus regarding the management approach for each scenario, with postsurgery observation alone remaining a popular strategy. Only 25% of respondents reported that their institution routinely tests for 1p/19q status in LGG, although 69% were of the opinion that all LGG patients should be tested. The majority (81%) preferred to use temozolomide rather than the procarbazine, lomustine, and vincristine combination as the first line chemotherapy for LGG, but only 44% would actually use it in this setting. Up front chemotherapy, prior to radiotherapy, would be considered by 52% of respondents for certain LGG patients. This survey assessed the management strategies for LGG since the updated RTOG 9802 data were presented. It demonstrates no consensus in the postoperative treatment approaches for LGG.